From the Inside Out: Gender Mainstreaming and Organizational Culture Within the Aid Sector - Lokot, Michelle (Frontiers in Sociology, 2021)
Many international non-government organizations (INGOs) implement interventions designed to promote gender equality, investing significant resources into embedding gender considerations into programmes through the strategy of gender mainstreaming. However, despite their altruistic mission, INGOs place less focus on addressing culture and power hierarchies within their organizations. This article suggests that many INGOs fail to walk the talk on gender equality. Through an analysis of recent challenges facing the development and humanitarian aid sector, including gaps in safeguarding and #AidToo, this paper emphasizes the importance of addressing gender equality from the inside out. It draws on feminist perspectives, the notion of the ‘deep structure’ of organizations and the author’s own experiences to argue for the need to address gendered, racial and colonial power hierarchies within the organizational culture of INGOs. The article argues that it is no longer sufficient to reduce gender mainstreaming and inclusion to programming interventions, and that INGOs need to reflexively and intentionally tackle power and inequalities within their own culture and structures.